Simultaneous Analysis of Independent Variables on Performance at the Department of Culture and Tourism Office - Sufitrayati Sufitrayati; Ulfia Ulfia; Cut Rusmina (International Conference on Multidisciplinary Research, 2021)
This study aims to determine the effect of accounting information systems, internal control, and task complexity on performance at the Aceh Culture and Tourism Office. The populations of this study were all employees of the Aceh Culture and Tourism Office as many as 186 people and the sampling technique used the Slovin technique to obtain 36 employees. The model used in this study is multiple linear regression analysis. The results showed that the accounting information system, internal control, and task complexity simultaneously affected the performance of the Aceh Culture and Tourism Office. The correlation coefficient (R) of 0.595 indicates that the correlation between the independent variable and the dependent variable is 59.5%, meaning that the performance at the Aceh Culture and Tourism Office has a moderate and positive correlation with the accounting information system. internal control and task complexity of 87.6%. While the coefficient of determination (R2) of 0.445 means that any change in performance variables can be explained by changes in accounting information system variables, internal control, and task complexity of 0.445 or 44.5%, and the remaining 55.5% is explained by other parties. Variable outside of this research can affect performance, for example, leadership style, financial accounting systems, internal control systems, financial management, and others.  Keywords: performance, accounting information systems, internal control, and task complexity.